1996
DOI: 10.1159/000262160
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and Urinary Fluoride Levels after 1-Month Use of Fluoride-Releasing Removable Appliances

Abstract: Forty children aged 8–10 years participated in this study. Half (n = 20) of them used orthodontic appliances which contained fluoride-releasing devices embedded in the lingual surface of the appliance and the other half used orthodontic appliances prepared from a fluoride-releasing acrylic polymer. Prior to the adjustment of appliances and after 1, 7, 14, 21 and 30 days salivary and urinary samples were collected and the fluoride concentrations were determined. The mean fluoride release was highest during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…This 'burst' effect has also been observed by other investigators in subjects without any systemic problems [Hörsted-Bindslev and Larsen, 1990;Cooley and McCourt, 1991;Alaçam et al,1996]. Also, the statistically significant difference (p !…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This 'burst' effect has also been observed by other investigators in subjects without any systemic problems [Hörsted-Bindslev and Larsen, 1990;Cooley and McCourt, 1991;Alaçam et al,1996]. Also, the statistically significant difference (p !…”
Section: Discussionsupporting
confidence: 81%
“…Cain et al [1994] employed 0.232 and 0.07 mg/day release rates and Alaçam et al [1996] employed a 0.32 mg F/day release rate in their in vivo controlled-release studies and observed an increase in salivary fluoride levels. In the present study, the selected release rate of 0.15 mg F/day was thought to be appropriate for a clinical investigation and the results showed a statistically significant increase in salivary fluoride concentrations, confirming the above studies; a salivary fluoride concentration of 150 times the normal concentration was maintained for 1 month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the oral hygiene problem has been much less intensively examined in patients with removable appliances [2,11,12,14,16,31,36,38,44,48]. Obviously, these patients have been regarded as representative of the average population, since their oral hygiene routines are in no way impeded.…”
Section: Introductionmentioning
confidence: 99%
“…Bei Patienten mit herausnehmbaren Geräten wurden Mundhygieneprobleme bisher relativ selten in Betracht gezogen [2,11,12,14,16,31,36,38,44,48] was performed by one of the authors (S.V. ), who had 5 years of clinical experience in periodontics and as an assistant professor in a university clinic.…”
Section: Introductionmentioning
confidence: 99%